A MODEL FOR IMPROVING THE MANAGEMENT SYSTEM AT ENERGY ENTERPRISES IN THE CONDITIONS OF THE DIGITAL ECONOMY - Савчук, Світлана (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
Abstract. The article researches theoretical and methodological approaches to building a model for improving the management system at energy enterprises in the conditions of the digital economy. The concept of improving the enterprise management system in the conditions of the digital economy has been developed, which is based on the provisions of the general theory of systems and takes into account the objective normative-legislative and subjective potentially predicted directions and ways of digital changes, which, unlike the existing ones, proclaims the ideology of systemic digital transformation on based on the substantiation of relevant areas of digital change, determines benchmarks for assessing the level of digital maturity and indicators of the results of digital transformation thanks to the use of digital economy technologies. The impact of digitalization of energy enterprises on their efficiency and expected results from digital transformation is studied. The principles of management in the conditions of digitalization are defined, including the principles of efficiency, optimality, flexibility, complexity, and safety. Features of management in the conditions of digitization are highlighted: high speed of management decision-making, interactivity of the environment and high speed of reaction to changes, orientation to a specific user, formation of a digital ecosystem, etc. On the basis of the defined conceptual principles of digital transformation, a model for improving the management system at energy enterprises in the conditions of the digital economy is proposed, which identifies functional areas of possible improvements based on taking into account the directions of necessary changes using the tools of digital transformation, which, unlike the existing ones, is based on agreed levels of the enterprise management system , in particular strategic, tactical and operational with the levels of its digital transformation, in particular strategic, business and infrastructure levels and the corresponding digital technologies at each of the identified levels of digital transformation.